Homeless dogs & melancholy apes : humans and other animals in the modern literary imagination - Brown, Laura, 1949- (Cornell University Press, 2010)
""I read Homeless Dogs and Melancholy Apes with great eagerness and found it to be a book of compelling interest, wonderful erudition, and nuanced, sophisticated analysis. It brings innovative perspectives and contexts to bear on core eighteenth-century topics and texts. Laura Brown takes up a leading concern in contemporary cultural studies--human-animal relations--and shows how modernity's paradigms of difference and alterity were articulated in the eighteenth century in ways sharply continous with our own."--Erin Mackie, Syracuse University" ""Homeless Dogs and Melancholy Apes engages with the long-standing conversation about otherness and also with the more recent and very lively conversation among humanists about animals. Laura Brown's work enhances understanding of how an important facet of eighteenth-century culture influenced and was incorporated into eighteenth-century literature."--Harriet Ritvo, Arthur J. Conner Professor of History, MIT" "In eighteenth-century England, the encounter between humans and other animals took a singular turn with the discovery of the great apes and the rise of bourgeois pet keeping. These historical changes created a new cultural and intellectual context for the understanding and representation of animal-kind, and the nonhuman animal has thus played a significant role in imaginative literature from that period to the present day. In Homeless Dogs and Melancholy Apes, Laura Brown shows how the literary works of the eighteenth century used animal-kind to bring abstract philosophical, ontological, and metaphysical questions into the realm of everyday experience, affording a uniquely, flexible perspective on difference, hierarchy, intimacy, diversity, and transcendence."